Legal Certainty of Land Certificates has been Issued Legally & Obtained In Good Faith (Review Decision Study Number 718 PK/PDT/2018) - Puspasari, Anneke Ivana; Suryani, Suryani; Samosir, Tetti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Land rights have described a person’s rights to ownership, must be registered in the land registry. This study uses a normative research method with qualitative analysis to obtain research results and discussions regarding the principle of good faith land ownership by a party for at least 20 (twenty) years and no other party has filed an objection or sued for 5 (five) years after the registration of the land in control with the Head of the local Land Office, until a certificate is legally issued as proof of ownership based on Article 32 paragraph (2) of the PP Land Registration in conjunction with Article 64 paragraph (1) PP No. 18/2021. To obtain legal certainty of ownership of land rights as has been canceled through a district court decision, the buyer filed a judicial review with an application using the legal basis of 32 paragraph (2) of the PP Land Registration and submitting new evidence (novum).